Contribution of Alexey Suvorin and His Newspaper Novoye Vremya into Russian Culture of the Second Half of 19th – Early 20th Century’ - N. V. Shevtsov; M. D. Krynzhina (Концепт: философия, религия, культура, 2021)
Novoye Vremya (The New Time) newspaper was considered as the leading daily periodical of the pre-revolutionary Russia. In 1876, Aleksey Suvorin, an outstanding Russian publisher and literary figure, became its owner and chief editor. He turned the newspaper into a source of information, which seriously influenced the public opinion in Russia. Novoye Vremya provoked constant interest among readers of all social levels. It was popular both among high-ranking government officials and people without any ranks, conservatives and liberals, people with higher education and those who did not even graduate a gymnasium. Newspaper stories were apprehensible not only for educated people but for any common person. Young and old, men and women liked Novoye Vremya. It had never forced its opinion and suggested the readers to make personal judgement through its reports. Suvorin managed to form the audience that valued the newspaper and believed in it. Not only Novoye Vremya stood out for its excellent materials on politics, economy, and non-fiction. In its reviews the newspaper gave a fair evaluation of the Russian authors’ works. Moreover, it became famous with the literary works of the top writers, the classics of Russian literature. Therefore, it is not by accident that the author of this article pays special attention to the cooperation between Novoye Vremya and the most known Russian writers of the second half of the 19th century and early 20th century. Thanks to Suvorin, the talent of Anton Chekhov, who started publishing his works in the newspaper under a different name, opened up. Novoye Vremya published the stories which were later included into his collection In the Twilight. Here he also published his famous novella The Duel. Despite the fact that Novoye Vremya was considered to be a newspaper rather than a literary magazine, it worked together with such writers as Leo Tolstoy, Nikolay Nekrasov, Nikolay Leskov, Mikhail Saltykov-Shchedrin, for whom the newspaper was not only a serious periodical but also a source of education and knowledge. In Soviet times the directive was to forget about Suvorin. And when they did remember, they certainly wrote about him as a reactionary, chauvinist, notorious monarchist. And if another major pre-revolutionary publisher I.D. Sytin was recognized by the Soviet government, although he lost his printing house and real estate, then Suvorin was in disgrace.